Providing Exclusive Asi To Working Mothers Reviewed From Motivational Factors And Length Of Parental Leave At Pt. Rhs Seruyan District Central Kalimantan - Nurmala Sari,; Candra Wahyuni,; Nining Istighosah, (Journal of Health Science Community, 2025)
Exclusive breastfeeding is very important for the growth and development of babies. A mother's motivation is crucial in providing exclusive breastfeeding for six months. Apart from that, working mothers can be affected by insufficient time for maternity and maternity leave. The aim of this research is to determine the relationship between exclusive breastfeeding for working mothers in terms of motivation factors and length of maternity leave at PT.RHS, East Seruyan Regency, Central Kalimantan. The design of this research is observational analytics with a cross-sectional time approach. The sample in this study was 32 mothers who had babies aged > 6 months at PT.RHS East Seruyan Regency, Central Kalimantan. The sampling method used a simple random sampling technique. Data collection uses a questionnaire. Data analysis used the chi square statistical test. The research results showed that of the 32 respondents, the majority did not provide exclusive breastfeeding, 20 people (62.5%), the majority with low motivation, 18 people (56.3%), and most of them took the appropriate length of maternity leave (3 months). before giving birth 1.5 months and after giving birth 1.5 months, namely 17 people (53.1%).Data analysis using statistical tests with Chi Square shows that the significance level is 0.000 < α = 0.05 so that H0 is rejected and H1 is accepted, thus there is a relationship between exclusive breastfeeding for working mothers in terms of motivation factors and length of maternity leave at PT.RHS, Seruyan Regency. East, Central Kalimantan. Meanwhile, the results of the logistic regression test showed a relationship between motivation and length of maternity leave with exclusive breastfeeding at PT.RHS, Seruyan Regency, Central Kalimantan. The motivation variable has a stronger relationship with exclusive breastfeeding with an OR value of 24.686 compared to the length of maternity leave variable with an OR value of 16.941. It was concluded that the success factor in providing exclusive breastfeeding was low motivation and insufficient maternity and maternity leave. So it is necessary to strengthen the motivation of breastfeeding mothers so they can provide exclusive breast milk.